Study of the Efficacy of Hydroxychloroquine in the Treatment of Actinic Cheilitis - Dr. Rajendra Kumar Sharma, Dr. Rahul Kumar Sharma (International Journal of Innovative Research in Medical Science, 2017)
Actinic cheilitis is a rare chronic and relapsing condition affecting predominantly the lower lip, which develops due to excess ultraviolet radiation exposure. It is a difficult and challenging condition to treat .So we decided to study the role of hydroxychloroquine in actinic cheilitis as this drug has shown positive results in similar conditions. All the patients who attended the dermatology clinic from March 2015 to March 2016 with the clinical diagnosis of actinic cheilitis and who fulfilled the inclusion and exclusion criteria were recruited for the study. The baseline workup including complete blood count, liver function test, renal function test and pre-hydroxychloroquine eye checkup was performed before initiating the drug. After that they were initiated on hydroxychloroquine and a lip emollient with weekly follow up. Our study showed that out of eighteen cases, nine patients showed complete resolution, five patients had partial improvement and four patients did not respond to hydroxychloroquine after three months of therapy. It is efficacious in actinic cheilitis due to its anti-inflammatory and systemic sunscreen like activity. Its actual role has to be further confirmed by large level case control study.